« A fairly typical boy », « a fairly typical girl » - Piccand, Laura (Emulations - Revue de sciences sociales, 2018)
Les stades dits de Tanner sont une série de photographies permettant d’évaluer le développement pubertaire des filles et des garçons. Utilisés dans la clinique et la recherche médicales contemporaines, leur histoire remonte aux années 1950. Cet article propose de revenir sur le contexte de production de cet artefact et d’interroger la façon dont il est partie prenante de la construction socio-historique de la binarité du sexe dit biologique. La puberté comme objet scientifique et médical est en effet un lieu crucial de production, de reproduction et de reconfiguration du genre.
Keywords: 1900-1999; 1950-1959; 1960-1969; angleterre; approches et analyses; cours; discipline; discours dominant; europe; inégalités; londres; patriarcat; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques

The lesbian South: Southern feminists, the women in print movement, and the queer literary canon - Harker, Jaime (The University of North Carolina Press, 2018)
In this book, Jaime Harker uncovers a largely forgotten literary renaissance in southern letters. Anchored by a constellation of southern women, the Women in Print movement grew from the queer union of women’s liberation, civil rights activism, gay liberation, and print culture. Broadly influential from the 1970s through the 1990s, the Women in Print movement created a network of writers, publishers, bookstores, and readers that fostered a remarkable array of literature. With the freedom that the Women in Print movement inspired, southern lesbian feminists remade southernness as a site of intersectional radicalism, transgressive sexuality, and liberatory space. Including in her study well-known authors—like Dorothy Allison and Alice Walker—as well as overlooked writers, publishers, and editors, Harker reconfigures the southern literary canon and the feminist canon, challenging histories of feminism and queer studies to include the south in a formative role.
Keywords: 1900-1999; 1950-1959; 1960-1969; amériques; approches et analyses; discours dominant; intersectionnalité; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; éditions; états-unis